Crop productivity, quality and nutrient uptake of pigeonpea (Cajadizus cajdillz) - wheat (Triticum - PALSANIYA, D R; AHLAWAT, I P S (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was carried out during 2003-2004 and 2004-2005 to study the response to sulphur and its sources in pigeonpea [Cajanus cajan (L.) Millsp.] - wheat [Triticum aestivum L. emend. Fiori & Paol.] cropping system on sandy loam soils of the Institute, New Delhi. Application of S to pigeonpea significantly enhanced the mean grain (pigeonpea 1.63 tonnesnla, wheat 4.23 tonnes/ha) and stalk (5.56 tonnes/ha) /straw yield (5.93 tonnes/ha), protein content